Integrated Waste Management in Supporting Awareness of Healthy Clean Communities in the Garut City Area - Anggraeni, Yunita; Ninin, Retno Hanggarani; Dalimunthe, Karolina Lamtiur; Rachman, Noer Fauzi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
This study aims to find out how waste management, especially in the Garut region. Waste management is an activity that requires integration between elements from up to downstream in order to create a clean and healthy environment. Proper and integrated waste management will keep up the balance of nature and cut the risk factors for disasters. This study uses ethnographic methods where researchers are directly in the field and follow people and groups who carry out waste disposal behavior in the community. The results of this study are the management of organic and inorganic waste at a personal level. In addition, local people’s wisdom in maintaining the ecology of their living space cannot be transferred in the form of awareness of waste management. On the other hand, the government does not yet have an integrated plan that will integrate personal, community and government levels in local waste management. The conclusion of this study is the limited understanding of the community only on the classification of types of waste with risk management forms such as the accumulation or burning of waste. Thus, awareness raising and integrated, simultaneous and continuous handling is needed so that the management of organic and non-organic waste becomes more right.